2005
DOI: 10.1021/ef0502296
|View full text |Cite
|
Sign up to set email alerts
|

Modeling on Pore Variation of Coal Chars during CO2Gasification Associated with Their Submicropores and Closed Pores

Abstract: When predicting the variation of pore structure during CO2 gasification of coal chars using the random pore model (RPM), it is impossible to calculate exactly the ψ parameter from the pore characteristics, which were obtained by means of N2 adsorption, such as BET surface area (denoted as N2 pore characteristics), of the char prior to gasification. The values of ψ, which were calculated from the pore characteristics of chars at various carbon conversions, should be fundamentally constant, unaffected by the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 27 publications
(31 reference statements)
6
31
0
Order By: Relevance
“…Similar to the changes of YFB at 1573K, the average pore diameter of YFB increases with increasing carbon conversion at 1273K. This phenomenon is mainly related with the pore expansion and coalescence [15] . Fig.3 shows variation of pore volume with carbon conversion during O 2 /CO 2 combustion.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Similar to the changes of YFB at 1573K, the average pore diameter of YFB increases with increasing carbon conversion at 1273K. This phenomenon is mainly related with the pore expansion and coalescence [15] . Fig.3 shows variation of pore volume with carbon conversion during O 2 /CO 2 combustion.…”
Section: Resultssupporting
confidence: 53%
“…The correlations between surface area of YFB and carbon conversion is shown in Fig.4. It can be seen that the surface area of YFB increases at 1273K at the initial stage of reaction, this phenomenon is mainly caused by generation of a large number of new pores and micropore expansion [15] , and then decreases when the carbon conversion is higher than above 50 %, which is mainly caused by pore collapse.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the model has received great successes in modeling gasification reactions of coal chars [5][6][7], it sometimes fails to describe the reactivity profiles of biomass chars, in which the reactivity increases with increasing conversion or exists a maximum in high conversion range. Two parameters were added in the random pore model to take inorganic element contents into account by Struis et al Modified random pore model has been recently used to investigate reactivity of biomass chars with fitting the experimental data [8][9][10].…”
Section: ) Biomass → Volatiles + Charmentioning
confidence: 99%
“…They attributed this phenomenon to the closed micropores in fresh chars and the re-opening of these micropores in initial reaction. Morimoto et al (2006) calculated the ψ values at various conversions during CO 2 gasification and found that the ψ values decreased dramatically with conversion. They suggested that the calculation of structural parameter ψ should be modified.…”
Section: Indication Of Char-slag Transition Char Conversionmentioning
confidence: 99%